The Impact of Financial Accounting for the Hospitality Industry on the Financial Statements : Afield Study on Sample of Hotels in the of KSA - Awad, Sana Ali (Archives of Business Research, 2023)
This study aimed at the importance of financial accounting for hospitality industry how they apply to the hospitality industry, and the responsibilities of a hospitality property's accounting department, advantages and drawbacks of various types of income statements, and the role of inventory in calculating profit. to research and greater cooperation among hospitality and other researchers the contribution to hospitality accounting and the broader accounting field could be significantly improved with amore in depth approach and greater , collaboration among hospitality and other researchers the contribution to hospitality accounting and the broader accounting field could be significantly improved . A significant hospitality accounting development over many years has been industry , notably hotels , restaurants and clubs in the United States where their first appearance , for hotels , was in 1926. In 1969 the UK produced the first of tow uniform systems for the hotel and catering sectors through. The study was conducted at the sample of hotels and it adopted the descriptive and historical approaches to collect literature review . It concludes that , Despite the increase in tourism revenues , management in the hospitality industry faces constant challenges for profit .